2013
DOI: 10.1186/1472-6963-13-462
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all: evaluating an intervention to reduce antibiotic prescribing for acute bronchitis

Abstract: BackgroundOveruse of antibiotics for upper respiratory tract infections (URIs) and acute bronchitis is a persistent and vexing problem. In the U.S., more than half of all patients with upper respiratory tract infections and acute bronchitis are treated with antibiotics annually, despite the fact that most cases are viral in etiology and are not responsive to antibiotics. Interventions aiming to reduce unnecessary antibiotic prescribing have had mixed results, and successes have been modest. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 36 publications
2
77
0
3
Order By: Relevance
“…Clinicians, for example, vary in their knowledge of antibiotic resistance and perceived barriers to changing their prescription behaviors (Ackerman, Gonzales, Stahl, & Metlay, 2013). The public may not know that non-essential use of antibiotics is harmful to themselves and others.…”
Section: What Is the Role Of Health Communication In Antibiotic Resismentioning
confidence: 99%
“…Clinicians, for example, vary in their knowledge of antibiotic resistance and perceived barriers to changing their prescription behaviors (Ackerman, Gonzales, Stahl, & Metlay, 2013). The public may not know that non-essential use of antibiotics is harmful to themselves and others.…”
Section: What Is the Role Of Health Communication In Antibiotic Resismentioning
confidence: 99%
“…181 A survey of physicians by Ackerman et al found that persistent perceived barriers to reducing prescribing indeed included time pressures and diagnostic uncertainty. 61 And, in another study, 28% of family physicians admitted to prescribing antibiotics "several times a…”
Section: Non-biomedical Factorsmentioning
confidence: 98%
“…28,40,44,54,55 It is apparent from the published literature that overprescribing of antibiotics by physicians is occurring within several areas of medicine in Canada [56][57][58] and globally. [59][60][61][62][63][64] Overprescribing of antibiotics has also been cited as being responsible for an increased incidence of allergic reactions-some of which may be fatal, drug toxicity, and an increased incidence of unfavourable interactions with other drugs taken by patients. 35,[65][66][67][68] Furthermore, since antibiotics only address symptoms of NTDCs and not the cause, the use of an antibiotic in the treatment of this type of emergency, even when necessary, often provides the patient with only temporary relief unless definitive dental care is also undertaken.…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Although most ARIs are caused by viruses, up to 60% of young children with ARIs are treated with antibacterial agents. [2] While unnecessary antibiotic usage may be reduced through a number of approaches, including patient and physician education, [3,4] physicians are often pressured to treat with antibiotics.…”
Section: Introductionmentioning
confidence: 99%